PENGARUH CAPITAL ADEQUACY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR) TERHADAP RETURN ON ASSETS (ROA) DENGAN NON PERFORMING FINANCING (NPF) SEBAGAI VARIABEL MODERATING (STUDI PADA BANK UMUM SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Evinta Amalia Nurhidayah; Fandil Fandil; sukarsono sukarsono (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Abstract. The phenomenon discussed in this research is the decrease of ROA which is the benchmark of banking performance. Besides, there is still gap result from previous research about Capital Adequacy Ratio and Financing to Deposit Ratio to Return On Assets, so this research add Non Performing Financing variable as moderating variable. The purpose of this study is to analyze and prove empirically the influence of Capital Adequacy Ratio and Financing to Deposit Ratio to Return On Assets and to analyze and prove empirically influence Non Performing Financing in moderating between Capital Adequacy Ratio and Financing to Deposit Ratio to Return On Assets. The population of this study is the Sharia Commercial Bank listed on the Indonesia Stock Exchange with a total sample of nine Sharia Commercial Banks listed on the Indonesia Stock Exchange for the period 2009-2016. Moderating Regression Analysis. The results of this study prove that Capital Adequacy Ratio has no effect on Return On Assets. Financing to Deposit Ratio has a significant effect on ROA. Non Performing Financing can moderate the influence between Capital Adequacy Ratio to Return On Assets. Non Performing Financing can not moderate the influence between Financing to Deposit Ratio to Return On Assets.